Social Shaping of Technologies for Community Development Redeployment of Information Communication Technologies among the Kelabit in Bario of the Kelabit Highlands - Poline, Bala (AIGI Global, 2009)
Using electronic-Bario (e-Bario) project in the Kelabit Highlands of Sarawak in East Malaysia, this chapter explores how the introduction of information communication technologies (ICT) as developmental tools have been mediated and reconfigured by webs of social relations and the intricate interplay of social, political and cultural conditions specific to different social and technical settings. One crucial factor conditioning the effects of the project has been the Kelabit’s own desire for, and expectations of, “development” and “progress.” This is a quest which ties in closely with two fundamental Kelabit concepts: doo-ness and iyuk. As a result, the social and economic effects of ICT have unfolded through countless open-ended strategic and everyday decisions made by the Kelabit themselves, who actively consume, apply and make use of objects, ideas and services in the Highlands.